Why is Tegula atra (Lesson) (Gastropoda) extinct from Patagonia? Biotic response to late Quaternary climate changes in the Southwestern Atlantic - Aguirre, Marina Laura; Richiano, Sebastián Miguel; Donato, Mariano Humberto; Farinati, Ester Amanda
The regional palaeobiogeographical context of Tegula atra (Lesson) revealed that it is a keystone endemic species within the marine Quaternary of Patagonia (Argentina, Southwestern Atlantic, SWA). A detailed systematic review together with field observations showed that it was absent from warmer than present Neogene sea-level episodes (e.g., late Miocene, ?Entrerriense?, ca. 10 Ma) and up to the mid-Pleistocene (Marine Isotope Stage 11 (MIS), ca. 400ka B.P.). By contrast, it exhibits an excellent and abundant, Late Pleistocene fossil record (MIS9, MIS7 and especially MIS5), along more than 1000 km between Río Negro and southern Santa Cruz provinces (Patagonia). A total of 130 collected bulk samples (complete sedimentary matrix and molluscan content) containing T. atra from more than 30 Pleistocene fossiliferous sites in 9 wider geographical areas (San Antonio Oeste, Puerto Lobos, Bahía Vera, Cabo Raso, Camarones, Bahía Bustamante, Caleta Olivia, Puerto Mazarredo, Puerto Deseado, San Julián) analyzed through multivariate and cladistic techniques confirmed its importance as a biostratigraphical/paleoclimate/palaeoceanographical signal within dominantly cool coastal settings. Additionally, morphometric analyses of Pleistocene (Patagonian) and modern (Pacific, Southeastern Pacific, SEP) specimens and Ancestral Areas analysis showed that after its first appearance in the SEP during the late Pliocene (cooling trend) it dispersed during the late Pleistocene into the SWA by rafting on macroalgae (Durvillaea antarctica) along the Cabo de Hornos and Malvinas (Falkland) currents, becoming extinct in the Mar Argentino (Magellan Malacological province) after the Last Interglacial (MIS5). Its absence today represents a climate change-driven range shift following the amelioration trend after the Last Glacial Maximum (LGM) and an independent evidence for palaeoceanographical changes at the Pleistocene/Holocene transition: changes in sea surface temperature (SST)(ca. 2°C higher), wind velocities (less), light (less), nutrient ...